Preparation of stable CdS nanoparticles in aqueous medium and their hydrogen generation efficiencies in photolysis of water - Girginer, B.; Galli, Giancarlo; Chiellini, Emo; Bicak, N. (Elsevier BV, 2009)
Abstract Diallyl dimethyl ammonium chloride (DADMAC)-N-vinyl 2-pyrrolidinone (NVP) copolymers were demonstrated to provide excellent stabilities for in situ generated CdS nanoparticles in aqueous medium. Nearly transparent and stable CdS dispersions (up to 0.1 M concentrations) were produced in 1% copolymer solutions. Experiments showed that, increasing DADMAC content induces greater stabilization. UV-visible spectroscopy, fluorescence spectroscopy, X-ray diffraction (XRD) and transmission electron microscopy (TEM) were used for characterization of the stable nanoparticles. TEM images showed snake-like alignment of nonspherical CdS nanoparticles with 50–70 nm of size, due to template effect of the cationically charged polymer. The CdS nanoparticles in aqueous medium showed reasonably high catalytic activities in photolysis of water, as inferred from hydrogen evolution measurements carried out in the absence and presence of noble metals, Pd and Pt. The highest hydrogen evolution rate (5.6 mL per gram of CdS in min) was detected in the presence of Pt metal, while illuminating with mercury lamp (160 W).